Computer-Aided Strategic Intervention Material (CA-SIM) in Chemistry 7 - Barrameda, Margie (IJBLE Scientific Publications Community Inc., 2024)
This research study developed Computer-Aided Strategic Intervention Materials (CA-SIM) in Chemistry 7 to promote students’ academic performance in science. The study aimed to answer four specific questions related to the format, steps in development, acceptability, and attitudes towards the CA-SIM. The study used a descriptive-developmental design and employed survey questionnaires and evaluation checklists for experts and students as research instruments. The data revealed that the CA-SIM is highly acceptable and satisfying for both teachers and students, with a rating of 2.57. The CA-SIM has ten lessons based on the competencies given by the new curriculum and follows the ADDIE model. The study concludes that the CA-SIM is a modern and effective way to teach Chemistry 7, making teaching and learning easier and more enjoyable. It is recommended that teachers can modify the CA-SIM based on the learners’ needs and contextualize the materials. The study provides a useful reference for other schools and teachers who teach Chemistry.